Recent Update on Management of Xerostomia: A Narrative Review (Nigerian Dental Journal, 2026)
Background: Xerostomia is a multifactorial condition with significant consequences for oral function and quality of life. While conventional diagnostic and treatment strategies remain essential, rapid advances in salivary diagnostics, imaging technologies, artificial intelligence, and regenerative therapies have expanded the clinical landscape. However, the clinical utility and translational readiness of these emerging approaches remain incompletely synthesised.Objectives: To review conventional and emerging diagnostic and therapeutic approaches for xerostomia and evaluate their clinical utility, translational readiness, and limitations.Methods: A narrative literature review was conducted using Google Scholar, MEDLINE, and PubMed databases. English-language publications from 2000 to 2025 were retrieved using combinations of keywords related to xerostomia, diagnosis, management, biomarkers, imaging, and emerging therapies. Clinical studies, systematic reviews, meta-analyses, and relevant narrative reviews were included.Results: Conventional diagnostic methods, including symptom assessment, clinical examination, and sialometry, remain essential but have limitations. Emerging approaches such as salivary biomarkers, advanced imaging, wearable sensors, and artificial intelligence show improved diagnostic potential. Traditional treatments focus on symptom relief and salivary stimulation, while novel therapies—including acupuncture, low-level laser therapy, intraoral devices, and regenerative approaches—demonstrate promising outcomes. However, their clinical application is limited by cost, accessibility, and insufficient validation.Conclusion: Conventional and emerging approaches should be viewed as complementary rather than competing strategies in xerostomia management. Although novel technologies offer substantial promise for improving diagnostic precision and therapeutic outcomes, further clinical validation and long-term evidence are required before widespread integration into routine practice.Keywords: Xerostomia; Hyposalivation; Salivary gland dysfunction; Diagnosis; Salivary biomarkers; Emerging therapies
Keywords: Xerostomia, Hyposalivation, Diagnosis, Treatment, Conventional, Novel, Methods